Processos erosivos e deposicionais costeiros no município de icapuí-ceará, Nordeste do Brasil - Chacanza, Mário Silva (2023)
Beaches are regions of the coastal zone where the effects of interaction between marine, terrestrial and atmospheric ecosystems are most often visualized, where natural agents, such as winds, tides, coastal currents and waves act more intensely and together. Anthropic agents also interfere in the coastal processes, modifying the natural dynamics of the coastal currents, interfering in the sedimentary contribution. These processes, whether natural or anthropic, may result in erosion or accretion. If erosion is intense and continuous, it will represent a serious problem, especially in densely occupied and economically important beaches, such as the Peroba and Redonda beaches in the municipality of Icapuí-Ceará that have, in recent time, registered erosive events. So, this work aimed to understand the erosive and depositional processes, through study of the shoreline variation in a short and medium term, on Peroba and Redonda beaches, and the vulnerability of the erosion like a form to subsidize the coastal management of the region. Satellite images, digital elevation models and orthomosaics generated from aerophotogrammetric data collected in the field with RPA were imported into the GIS environment where they were vectorized, shoreline variation rates, volume difference and the value of the coastal vulnerability index were calculated. In the medium term, between 2005 and 2020, the results indicated that the values provided by the End Point Rate and Linear Regression were -0.54 and -0.47 m/year, respectively, indicating that the shoreline remained stable at about 82.81% (4,200 m) and 84.98% (4,310 m). The results generated from RPA data (2020-2021), indicated that at Peroba beach the shoreline remained stable at about 0.87 m/yr, where the volume variation indicated a positive sediment balance on the order of 18,815 m3. At Redonda beach the coastline varied around 1.27 m/year, where the variation in volume indicated a negative balance of sediments in the whole period of -1,230 m3. Regarding sediments, the beach system was mostly characterized by very fine and fine sands. The variation in volume indicated trends similar to those of the coastline, with greater intensity of deposition in the western portion of each beach. It was observed that relatively stable sectors have anthropic influence by the construction of erosion containment structures. The greater deposition in the western subsectors of the two beaches may be associated with the erosion of the eastern subsector driven by wave action near the headlands and tidal currents associated with episodes of supermoon and high tide, combined with other sources of sediment contribution that feed the beaches through coastal drift. In relation to sensitivity at erosion, beaches presented three levels of vulnerability: moderate with 58% (2,940 m), high with 41% (2,100 m) and very high with 1% (30 m). This work presents robust information that will assist in decision making and management of the studied coastal zone.